Endoscopic transpterygoid approach to a mass in a child. (February 2018) - Lee, Dong Hoon; Baek, Hee Jo; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract: The endoscopic transterygoid approach to the petrous apex is a feasible/alternative approach in carefully selected patients with specific favorable anatomy, even children. This approach, unlike traditional approaches, spares cochlear and vestibular function. We report a case of a six-year-old boy with embryonal rhabdomyosarcoma of the petrous apex that was diagnosed via the endoscopic transpterygoid approach.